1jikannsuu kiso04 1 5test

10 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 3xy5 = 0

5 −5

5

−5

x y

O

(2) −y−4x−4 = 0

5 −5

5

−5

x y

O

(3) y−x+ 1 = 0

5 −5

5

−5

x y

O

(4) −x+y=−5

5 −5

5

−5

x y

O

(5) −y−2x−2 = 0

5 −5

5

−5

x y

O

(6) y+ 2x= 1

5 −5

5

−5

x y

O

(7) −x−y−5 = 0

5 −5

5

−5

x y

O

(8) y+ 3x= 5

5 −5

5

−5

x y

O

(9) 2x+y=1

5 −5

5

−5

x y

O

(2)

(1) 3xy5 = 0

5 −5

5

−5

x y

O

(2) −y−4x−4 = 0

5 −5

5

−5

x y

O

(3) y−x+ 1 = 0

5 −5

5

−5

x y

O

(4) −x+y=−5

5 −5

5

−5

x y

O

(5) −y−2x−2 = 0

5 −5

5

−5

x y

O

(6) y+ 2x= 1

5 −5

5

−5

x y

O

(7) −x−y−5 = 0

5 −5

5

−5

x y

O

(8) y+ 3x= 5

5 −5

5

−5

x y

O

(9) 2x+y=1

5 −5

5

−5

x y

O

(3)

(1) −3x+y = 3

5 −5

5

−5

x y

O

(2) −y−3x= 3

5 −5

5

−5

x y

O

(3) −y−3x=−6

5 −5

5

−5

x y

O

(4) y−3x+ 1 = 0

5 −5

5

−5

x y

O

(5) −y+ 4x−5 = 0

5 −5

5

−5

x y

O

(6) −y+ 3x= 3

5 −5

5

−5

x y

O

(7) x+y= 6

5 −5

5

−5

x y

O

(8) y−2x+ 3 = 0

5 −5

5

−5

x y

O

(9) x−y+ 1 = 0

5 −5

5

−5

x y

O

(4)

(1) −3x+y = 3

5 −5

5

−5

x y

O

(2) −y−3x= 3

5 −5

5

−5

x y

O

(3) −y−3x=−6

5 −5

5

−5

x y

O

(4) y−3x+ 1 = 0

5 −5

5

−5

x y

O

(5) −y+ 4x−5 = 0

5 −5

5

−5

x y

O

(6) −y+ 3x= 3

5 −5

5

−5

x y

O

(7) x+y= 6

5 −5

5

−5

x y

O

(8) y−2x+ 3 = 0

5 −5

5

−5

x y

O

(9) x−y+ 1 = 0

5 −5

5

−5

x y

O

(5)

(1) −y+x+ 6 = 0

5 −5

5

−5

x y

O

(2) −y+ 4x= 3

5 −5

5

−5

x y

O

(3) −2x+y−6 = 0

5 −5

5

−5

x y

O

(4) 4x+y= 2

5 −5

5

−5

x y

O

(5) y+ 4x= 4

5 −5

5

−5

x y

O

(6) 2x+y= 3

5 −5

5

−5

x y

O

(7) −4x+y−6 = 0

5 −5

5

−5

x y

O

(8) −y+ 4x= 6

5 −5

5

−5

x y

O

(9) −y+ 3x= 4

5 −5

5

−5

x y

O

(6)

(1) −y+x+ 6 = 0

5 −5

5

−5

x y

O

(2) −y+ 4x= 3

5 −5

5

−5

x y

O

(3) −2x+y−6 = 0

5 −5

5

−5

x y

O

(4) 4x+y= 2

5 −5

5

−5

x y

O

(5) y+ 4x= 4

5 −5

5

−5

x y

O

(6) 2x+y= 3

5 −5

5

−5

x y

O

(7) −4x+y−6 = 0

5 −5

5

−5

x y

O

(8) −y+ 4x= 6

5 −5

5

−5

x y

O

(9) −y+ 3x= 4

5 −5

5

−5

x y

O

(7)

(1) y+x−4 = 0

5 −5

5

−5

x y

O

(2) x+y−3 = 0

5 −5

5

−5

x y

O

(3) −4x−y= 4

5 −5

5

−5

x y

O

(4) y+x= 3

5 −5

5

−5

x y

O

(5) −3x+y−6 = 0

5 −5

5

−5

x y

O

(6) x+y+ 1 = 0

5 −5

5

−5

x y

O

(7) −y+ 2x=−2

5 −5

5

−5

x y

O

(8) −y+x= 2

5 −5

5

−5

x y

O

(9) y+x+ 1 = 0

5 −5

5

−5

x y

O

(8)

(1) y+x−4 = 0

5 −5

5

−5

x y

O

(2) x+y−3 = 0

5 −5

5

−5

x y

O

(3) −4x−y= 4

5 −5

5

−5

x y

O

(4) y+x= 3

5 −5

5

−5

x y

O

(5) −3x+y−6 = 0

5 −5

5

−5

x y

O

(6) x+y+ 1 = 0

5 −5

5

−5

x y

O

(7) −y+ 2x=−2

5 −5

5

−5

x y

O

(8) −y+x= 2

5 −5

5

−5

x y

O

(9) y+x+ 1 = 0

5 −5

5

−5

x y

O

(9)

(1) y+x= 6

5 −5

5

−5

x y

O

(2) −3x−y+ 5 = 0

5 −5

5

−5

x y

O

(3) −y−4x+ 3 = 0

5 −5

5

−5

x y

O

(4) −2x−y = 3

5 −5

5

−5

x y

O

(5) −3x−y= 4

5 −5

5

−5

x y

O

(6) 3x−y−5 = 0

5 −5

5

−5

x y

O

(7) −y−x−6 = 0

5 −5

5

−5

x y

O

(8) y−3x= 6

5 −5

5

−5

x y

O

(9) 3x+y+ 1 = 0

5 −5

5

−5

x y

O

(10)

(1) y+x= 6

5 −5

5

−5

x y

O

(2) −3x−y+ 5 = 0

5 −5

5

−5

x y

O

(3) −y−4x+ 3 = 0

5 −5

5

−5

x y

O

(4) −2x−y = 3

5 −5

5

−5

x y

O

(5) −3x−y= 4

5 −5

5

−5

x y

O

(6) 3x−y−5 = 0

5 −5

5

−5

x y

O

(7) −y−x−6 = 0

5 −5

5

−5

x y

O

(8) y−3x= 6

5 −5

5

−5

x y

O

(9) 3x+y+ 1 = 0

5 −5

5

−5

x y

O

Updating...

参照

Updating...

関連した話題 :